Estudo in vitro de dentifrícios fluoretados e suplementados com trimetafosfato de sódio nanoparticulado sobre a erosão dentária - Santos, Vinicius Rodrigues dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to evaluate the effect of conventional toothpaste and supplemented with nano-sized sodium trimetaphosphate in dental erosion in vitro. Bovine enamel blocks (4 mm x 4 mm, n = 60) were selected from the initial surface hardness (SHi) and then divided into 5 groups of experimental dentifrices (n = 12): No F/TMP/TMPnano (Placebo); 1100 ppm F (1100 ppm F); 1100 ppm F associated with 3% TMP micrometric (1100 TMP); 1100 ppm F associated with 3% TMP nano-sized (1100 TMPnano) and 5000 ppm F (5000 ppm F). The erosive challenge was produced by the citric acid, for 5 minutes (4x / day) for 5 days. After the challenges, were determined the final surface hardness (SHF), enamel wear (uM) and toughness in longitudinal section (ΔKHN). Data were subjected to analysis of variance (one option) followed by Student-Newman-Keuls test (p < 0.001). SHF values were significantly higher in the groups treated with the toothpaste supplemented with TMP, TMPnano and 5000 ppm F, when compared to placebo and 1100 ppm F (p < 0.001); there was no significant difference between 1100 and 5000 ppm TMPnano F (p = 0.202) for the three analyzes (SHF; wear and ΔKHN). The toothpastes 1100 TMPnano and 5000 ppm F had a greater protective effect when compared to the conventional toothpastes (1100 ppm F) for wear, SHf and ΔKHN variables (p < 0.001). From the results, it is concluded that the addition of 3% TMP nano-sized in conventional toothpaste (1100 ppm F) promoted a synergistic protective effect against erosive wear of the enamel when compared to their counterparts, reaching protection levels similar to those observed for toothpaste 5000 ppm F

O objetivo deste estudo foi avaliar a ação de dentifrícios fluoretados e suplementados com trimetafosfato de sódio nanoparticulado, na erosão dentária in vitro. Blocos de esmalte bovino (4 mm x 4 mm, n = 60) foram selecionados através da dureza de superfície inicial (SHi) e a seguir divididos em 5 grupos, de acordo com os dentifrícios experimentais (n = 12): Sem F/TMP/TMPnano (Placebo); 1100 ppm de F (1100 ppm F); 1100 ppm F + 3% de TMP micrométrico (1100 TMP); 1100 ppm de F + 3% de TMP nanoparticulado (1100 TMPnano) e 5000 ppm F (5000 ppm F). O desafio erosivo foi produzido pelo ácido cítrico, por 5min (4x/dia), durante 5 dias. Após os desafios, foram determinadas a dureza de superfície pós-erosão (SHf), desgaste do esmalte (μm) e dureza em secção longitudinal (ΔKHN). Os dados foram submetidos à análise de variância (1 critério) seguido pelo teste Student-Newman-Keuls (p < 0,001). Os valores de SHf foram significativamente maiores nos grupos tratados com os dentifrícios suplementados com TMP, TMPnano e 5000 ppm F, quando comparado ao Placebo e 1100 ppm F (p < 0,001); não foi observada diferença significativa entre 1100 TMPnano e 5000 ppm F (p = 0,202) para as três análises (SHf; desgaste e ΔKHN). Os dentifrícios 1100 TMPnano e 5000 ppm F tiveram um efeito protetor maior quando comparado com o controle positivo (1100 ppm F) para as variáveis desgaste, SHf e ΔKHN (p < 0,001). Mediante os resultados, conclui-se que a adição de 3% TMPnano em dentifrícios convencionais (1100 ppm F) promoveu um efeito protetor sinérgico contra o desgaste erosivo do esmalte quando comparado com os seus homólogos, atingindo níveis de proteção semelhantes aos observados para o dentifrício 5000 ppm F
Keywords: Esmalte dentário; Flúor; Fosfatos; Erosão dentária; Dentifrícios; Dental enamel